Особливості образної номінації переживань в ідіостилі Наталени Королевої (на матеріалі повісті «1313») - Кость, Ірина; Kost, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
Стаття присвячена проблемі визначення ідіостильової манери вербалізації внутрішньої сфери персонажів повісті «1313» Наталени Королевої. Увагу зосереджено на особливостях маніфестації емоцій засобами образної номінації, а саме: метафорами, фразеологізмами, порівняннями. Визначено асоціативні основи образних найменувань емоцій. The article is dedicated to the problem of determination of idiostyle manner of inner world verbalization of heroes in the novel «1313» by Natalena Koroleva. The attention is drawn to emotion manifestation by means of image nomination in the text, namely: by means of metaphors, phraseological units, similes. The associations have been defined which have become the basis for image nomination of emotions. The use of heart and soul images in phraseologisms and metaphors for emotion nomination has been determined. The emotional states for the use of which the author uses image nomination have been specified. The peculiarities of metaphor, phraseological unit and simile use in the function of verbalizers of emotions by Natalena Koroleva have been clarified.
The peculiarities of image nomination of emotions in idiostyle of Natalena Koroleva (on the basis of the novel «1313»)
Keywords: емоція; вербалізація; фразеологізм; метафора; порівняння; Наталена Королева; emotion; verbalization; phraseological unit; metaphor; simile; Natalena Koroleva